Smoking Cessation Counseling in Family Medicine - Tracy L. Johns; Karl Metzger; Elizabeth Lawrence (SAGE Publishing, 2014)
Background: Tobacco use causes significant morbidity and mortality. Although studies show that people who smoke cigarettes are more likely to quit when health care providers recommend cessation, many patients may not perceive that advice was given. Purpose: Using a survey, to determine if a provider visual cue improves patient perception that smoking cessation counseling occurred. Another objective is to evaluate effects on frequency of specific counseling elements. Methods: This was a quasi-experimental intervention study with a pre-post test design. The intervention was a quitline reference card attached to the billing form as a prompt for providers to address smoking cessation. The patient survey included 6 elements, each assigned 1 point. The outcomes were the mean survey summary score preintervention compared to postintervention and the distribution of individual elements. Results: Preintervention, 40 patients who smoke cigarettes completed the survey; 46 patients were enrolled postintervention. The groups were similar, with no significant differences in age, gender, or race/ethnicity. Mean survey summary scores pre- and postintervention were 4.1 and 5.1, respectively ( P < .05). Compared with preintervention, more patients perceived the recommendation for a smoking cessation course postintervention (40% vs 83%, P < .05). No significant differences in perceptions of other counseling elements were found. Conclusions: Providing a visual cue such as a quitline card is an effective and inexpensive means of prompting a provider to discuss smoking cessation and can be easily integrated into practice. Our results indicate that this strategy improves patient perceptions of counseling with potential to improve community health through education.